Transformasi Motivasi Belajar Bahasa Arab Mahasiswa Baru Indonesia pada Tahun Pertama di Universitas Tabuk - Paujiyah, Nadatul; Firdaus, Muhammad Ali; Odang (Jurnal Internasional Pendidikan Bahasa Arab, 2025)
Indonesian students pursuing Arabic studies in Saudi Arabia often face a significant decline in learning motivation during their first year due to culture shock, language barriers, and academic pressure. This phenomenon represents a complex inner journey of adaptation that has not been deeply explored within the specific context of the University of Tabuk. This study aims to analyze the transformation of Arabic learning motivation among newly enrolled Indonesian students at the University of Tabuk during their first academic year. It seeks to describe the dynamic shifts in motivation and identify the internal and external factors influencing these changes. Employing a descriptive qualitative phenomenological approach, data were collected through in-depth semi-structured interviews. The data were analyzed using a phenomenological analysis model to identify significant themes regarding the participants' lived experiences. The results reveal a dynamic trajectory where motivation initially surges due to religious and academic idealism, declines caused by adaptation challenges, and eventually restabilizes through a shift toward intrinsic motivation. Key factors facilitating this resilience include a supportive academic environment, the integration of spiritual values (ibadah), social connectedness, and the utilization of technology for independent learning. This research offers novelty by identifying spiritual values as a unique primary anchor for resilience, distinguishing Indonesian students from general international students who rely mostly on academic integration. The study suggests that future research employ longitudinal approaches over the full four-year program and comparative studies across other Middle Eastern universities to validate whether the "Tabuk experience" is a regional phenomenon.